Effects of Straps and Movements on the Pressure Distribution Induced by a Backpack (Journal of Fiber Bioengineering and Informatics, 2019)
Backpacks have been widely used to increase load carriage capacity, but the pressure at the body surfacemay cause discomfort or pains. Previous studies revealed that chest straps and hip belts of backpackhelped to relieve the discomfort feeling, but how the pressure changes are still unclear. In this study, theinfluence of strap tying and the posture change on the pressure distribution were investigated. A dailybackpack with 5kg load was used in the experiment. Five young females carried the backpack to stand,walk and jog. The pressures were measured at the shoulder, waist and hip, which are the primary loadbearing regions. The trunk forward lean angle (TFL) was captured by using the Vicon motion capturesystem. Results showed that tying both the chest strap and hip belt reduced the shoulder pressure andincreased the pressure at the hip and waist. From standing, walking to running, TFL increased graduallyand the pressure transferred from shoulder to back and hip. These findings help us to better understandand quantify the load carrying performance of a backpack.
Keywords: Backpack; Pressure Distribution; Straps; Lean Angle